THE EFFECT OF GEOGEBRA-BASED INSTRUCTION ON THE CONCEPTUAL UNDERSTANDING OF LINEAR ALGEBRA AMONG INFORMATICS ENGINEERING STUDENTS - Mey Chyntia Yesaya; Sri Widyanti Ginting; Melda Dahoklory (JURNAL MathEdu (Mathematic Education Journal), 2026)
The integration of digital technology into mathematics education has become an essential strategy for improving students' conceptual understanding, particularly in abstract subjects such as Linear Algebra. GeoGebra, an interactive mathematical software, provides dynamic visualizations that enable students to explore mathematical concepts more effectively. This study aims to examine the effect of GeoGebra-based instruction on the conceptual understanding of Linear Algebra among Informatics Engineering students. A quantitative approach employing a quasi-experimental design with a pretest–posttest control group was used. The participants consisted of undergraduate Informatics Engineering students enrolled in a Linear Algebra course, divided into an experimental group receiving GeoGebra-based instruction and a control group receiving conventional instruction. Data were collected using a conceptual understanding test administered before and after the intervention. The data were analyzed using descriptive statistics and an independent samples t-test to determine significant differences between the two groups. The findings indicate that students who learned through GeoGebra-based instruction demonstrated significantly higher conceptual understanding than those who received conventional instruction. The dynamic visualization and interactive features of GeoGebra facilitated students in exploring vector operations, matrix transformations, and systems of linear equations, thereby strengthening their conceptual comprehension and problem-solving abilities. These results suggest that GeoGebra is an effective instructional tool for enhancing conceptual understanding in Linear Algebra courses, particularly for Informatics Engineering students. The study recommends integrating GeoGebra into higher education mathematics curricula to promote active learning and improve students' mathematical competence.